Tanggung Jawab Negara Atas Perlindungan Keselamatan dan Kesehatan Kerja (K3) dalam Perspektif Undang-Undang Ketenagakerjaan - Nikmah Dalimunthe; Mohammad Rafli; Rossy Al Jabar (Universitas Kapuas, 2026)
Occupational Safety and Health (OSH) constitutes a fundamental workers’ right that must be guaranteed by theState as part of its human rights obligations. Within the employment relationship, the State bears a constitutional duty to ensure safe, healthy, and dignified working conditions. This article examines State responsibility for OSH protection under Indonesian labour law. It aims to identify the normative basis and forms of State responsibility, evaluate the effectiveness of the regulatory framework, and assess the implementation of OSH standards across employment sectors. The research adopts a normative juridical method, employing statutory and conceptual approaches, with data derived from legislation and scholarly literature published within the last decade. The study finds that although Indonesia has established OSH obligations through various legislative instruments, enforcement remains suboptimal, particularly in the informal sector, small and medium enterprises, and regions with limited supervisory capacity. Insufficient labour inspection mechanisms and the limited number of labour inspectors contribute to recurrent non-compliance with statutory OSH standards. The article concludes that State responsibility in ensuring effective OSH protection requires regulatory reinforcement, strengthened supervisory institutions, and enhanced inter-agency coordination to secure comprehensive labour protection.